1999
DOI: 10.1097/00004032-199906000-00005
|View full text |Cite
|
Sign up to set email alerts
|

Solubility of Various Forms of Strontium Titanate in Lungs

Abstract: At the In-Tank Precipitation Facility of the Savannah River Site, strontium and other radionuclides are removed from high-level radioactive waste and sent to the Defense Waste Processing Facility. Strontium removal is accomplished by adsorption using a slurry that includes monosodium titanate, which forms strontium titanate with unknown lung solubility characteristics. The purpose of this study was to determine the solubility of strontium titanate in the form created at the In-Tank Precipitation facility. An i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 0 publications
2
4
0
Order By: Relevance
“…During the first 2 weeks, 5.2 μg of Sr is released from 1 cm 2 of the surface, and in the subsequent 2 weeks, the release amount is about 3.3 μg/cm 2 . The measured dissolution rates from SrTiO 3 have the same order of magnitude as that reported in ref . According to ref , Ti and Sr do not dissolve congruently.…”
Section: Resultssupporting
confidence: 81%
“…During the first 2 weeks, 5.2 μg of Sr is released from 1 cm 2 of the surface, and in the subsequent 2 weeks, the release amount is about 3.3 μg/cm 2 . The measured dissolution rates from SrTiO 3 have the same order of magnitude as that reported in ref . According to ref , Ti and Sr do not dissolve congruently.…”
Section: Resultssupporting
confidence: 81%
“…Excretion was predominantly faecal, indicating that the material was relatively insoluble. In-vitro dissolution tests performed with various forms of 90 SrTiO 3 from high-level radioactive waste facilities (Anderson et al ., 1999) showed that 97% of the strontium remained undissolved at 181 d, indicating assignment to Type S. Absorption parameter values calculated here were f r = 0.009, s r = 0.7 d −1 , and s s = 1.2×10 −4 d −1 . In a parallel in-vivo study, the biokinetics of strontium and titanium were followed for 30 d after intratracheal instillation of stable SrTiO 3 in rats.…”
Section: Strontium (Z = 38)mentioning
confidence: 99%
“…These ingredients have acceleration or suppression effects on dissolution. Therefore, solubility measurement experiments using pseudo biological fluids have been performed to evaluate the solubility of many kinds of materials such as heavy metal compounds [8][9][10][11][12] , mineral dusts including asbestos substitutes [13][14][15][16] , soils 17) , radio active aerosols [18][19][20] and other low solubility materials [21][22][23] into biological fluid.…”
mentioning
confidence: 99%